Taḥlῑl Ikhtibār Kafā`ah al-Lugah al-‘Arabiyyah li an-Nāṭiqῑna bigairihā fī Jāmi’ah Sulṭān Syarῑf Qāsim al-Islāmiyyah al-Ḥukūmiyyah Riau - Halomoan Halomoan; Faizal Mahmoud Adam Ibrahim; Uril Bahruddin (LISANIA: Journal of Arabic Education and Literature, 2022)
This study assessed the items quality of the Test of Arabic as a Foreign Language (TOAFL) conducted at Sultan Syarif Kasim State Islamic University (UIN) Riau, including the questions’ validity and reliability, difficulty level, and discriminating power. It used the descriptive quantitative method. The data were collected by tests and documentation, and then analyzed using SPSS 25. Regarding question validity, it was found that 35 items (25%) were valid, and 105 (75%) items were invalid. Meanwhile, the reliability score was 0.856. while judging from the level of difficulty, it was found that the easy category included 40 items (28.57%), the medium category included 56 questions (40%), and the difficult category included 44 questions (31.43%). In terms of discriminating power, 36 questions (25,71% were in the excellent category, 21 questions (15%) were good, and 83 questions (59,29%) were considered in the bad category.